Regulation of 4E-BP1 activity in the mammalian oocyte - Jansova, Denisa; Koncicka, Marketa; Tetkova, Anna; Cerna, Renata; Malik, Radek; Del Llano, Edgar; Kubelka, Michal; Susor, Andrej (Cell Cycle, 2017)
Fully grown mammalian oocytes utilize transcripts synthetized and stored during earlier development. RNA localization followed by a local translation is a mechanism responsible for the regulation of spatial and temporal gene expression. Here we show that the mouse oocyte contains 3 forms of cap-dependent translational repressor expressed on the mRNA level: 4E-BP1, 4E-BP2 and 4E-BP3. However, only 4E-BP1 is present as a protein in oocytes, it becomes inactivated by phosphorylation after nuclear envelope breakdown and as such it promotes cap-dependent translation after NEBD. Phosphorylation of 4E-BP1 can be seen in the oocytes after resumption of meiosis but it is not detected in the surrounding cumulus cells, indicating that 4E-BP1 promotes translation at a specific cell cycle stage. Our immunofluorescence analyses of 4E-BP1 in oocytes during meiosis I showed an even localization of global 4E-BP1, as well as of its 4E-BP1 (Thr37/46) phosphorylated form. On the other hand, 4E-BP1 phosphorylated on Ser65 is localized at the spindle poles, and 4E-BP1 phosphorylated on Thr70 localizes on the spindle. We further show that the main positive regulators of 4E-BP1 phosphorylation after NEBD are mTOR and CDK1 kinases, but not PLK1 kinase. CDK1 exerts its activity toward 4E-BP1 phosphorylation via phosphorylation and activation of mTOR. Moreover, both CDK1 and phosphorylated mTOR co-localize with 4E-BP1 phosphorylated on Thr70 on the spindle at the onset of meiotic resumption. Expression of the dominant negative 4E-BP1 mutant adversely affects translation and results in spindle abnormality. Taken together, our results show that the phosphorylation of 4E-BP1 promotes translation at the onset of meiosis to support the spindle assembly and suggest an important role of CDK1 and mTOR kinases in this process. We also show that the mTOR regulatory pathway is present in human oocytes and is likely to function in a similar way as in mouse oocytes.
Keywords: Animals; aparát dělícího vřeténka; transportní proteiny; fosfoproteiny; proteosyntéza; TOR Serine-Threonine Kinases; Gene Expression Regulation, Developmental; Cell Cycle; Oocytes; lidé; Phosphoproteins; Mice; oocyty; myši; buněčný cyklus; Carrier Proteins; fosforylace; proteinkinasa CDC2; Protein Biosynthesis; Spindle Apparatus; CDC2 Protein Kinase; zvířata; TOR serin-threoninkinasy; vývojová regulace genové exprese; Phosphorylation; Humans